Penerapan Algoritma Floyd Warshall Dalam Aplikasi Penentuan Rute Terpendek Mencari Lokasi BTS (Base Tower Station) Pada PT.GCI Palembang - Vera Apriliani Nawagusti (Jurusan Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2018)
For PT.GCI Palembang optimization of the shortest route is needed in the process of finding the location of BTS (Base Tower Station) because with the optimization of the shortest route determination can assist the technician in optimizing the distance to the location of BTS needs to be done maintenance and repair so as to increase the efficiency of time and the required costs. The shortest route problem is a problem in finding the path between two vertices on a weighted graph that has a combined value of the number of weights on the side of the graph passed by the minimum number. In this research using Floyd Warshall algorithm to determine the shortest route. Where the Floyd Warshall algorithm can compare all track opportunities in the graph for each side of all the nodes it passes to the least amount. Based on the results of calculations from this research obtained the shortest route that is from point 1 – 4- 3 – 2 that is equal to 10,9 km